The expansion of María Rosa Lojo’s poetry in "Esperan la mañana verde" and "Historias del Cielo" (Anclajes, 2021)
There are two identifiable moments in María Rosa Lojo’s lyrical work, gathered in Bosque de ojos (2011): one composed of Visiones (1984) and Forma oculta del mundo (1991), and another of Esperan la mañana verde (1998) and Historias del Cielo (2011). While in the first two books the self-absorption of the medium-poet in charge of the enunciation prevails, in the final two Lojo’s poetics expands (in a gesture that may be understood as decolonial) in order to integrate references and characters from historically marginalized traditions and silenced by modern reasoning. This incorporation means that the search for the Other, a central aspect of Lojo’s poetic work, is now undertaken with a more expansive and narrative language, more drawn to astonishment and irony, far from the serious, fearful and oracular tone of the earlier books. This turn can be read as the move from the medium-poet to the shaman-poet, a concept Lojo has examined in some of her metapoetic texts.
Keywords: María Rosa Lojo; contemporary Argentinian poetry; decoloniality; XXI century